Aesthetic Adaptation as a Culture Strategy in Preserving the Local Creative Potentials - Triyanto, Triyanto; Mujiyono, Mujiyono; Sugiarto, Eko (Universitas Negeri Semarang, 2017)
This study aims to understand and explain the problems of aesthetic adaptation through the development of ceramic art design in Mayong Lor Village as a cultural strategy in facing market competition to maintain the local characteristics. The research data was through by participant observation technique, in-depth interview, and document data tracking. The results show the following: First, the type of ceramic products can be classified into four categories, namely: 1) celengan (piggy banks), (2) children›s toys/remitance (keg, jars, cups, glasses, plates, paso, teapots, earrings, angklo, kekep) , (3) glassware for household purposes, such as jugs, kendil, padasan, and cowek, (4) decorative items (vases, jars, pots, wuwungan tiles, pencil pot, souvenirs, and carving. Aesthetically, the expression on ceramic pottery of Mayong Lor Village is simple and non-complicated as well as prioritizes the aspect of physical function which is oriented to economic value. Second, the social and cultural environment of Mayong Lor society creates typical patterns of interaction and lifestyle (with the support of its natural resources) resulting in the process of skill transfer of ceramic pottery traditionally from generation to generation and produces a unique and simple ceramic product. Third, in the midst of the strong influence of modern industrial pressures, the craftsmen struggle in the process of creativity by performing an aesthetic adaptation to develop new design with new artistic and economical values as the embodiment of a cultural strategy to maintain the creative potential of their local arts.